Urgency of Legal Protection for Religious Scholars in Articles on Blasphemy from the Perspectives of Criminology and Victimology - Fithry, Abshoril; Sjaifurrachman, Sjaifurrachman (PT. Riset Press International, 2024)
The urgency lies in the ambiguous definition, which allows this article to be interpreted in various ways and potentially forces anyone into the realm of criminal law. This is found in Article 156a, which states that anyone who deliberately expresses sentiments or performs acts essentially hostile, abusive, or blasphemous against a religion practiced in Indonesia shall be punished with imprisonment for a maximum of 5 years in public. The phrase